(untitled) (Journal of Fatima Jinnah Medical University, 2025)
Background: Breast cancer is a global health concern, especially in Europe and America, with higher incidence and mortality rates. HER2-positive breast cancer accounts for 20-25% of diagnoses, known for its aggressive behavior. To assess HER2 status, various methods are available, including PCR, IHC, FISH, and CISH. Immunohistochemistry (IHC) and Fluorescence in Situ Hybridization (FISH) are the primary techniques for HER2 evaluation. IHC and FISH are the predominant methods employed for evaluating HER2 status. IHC gauges the expression of the HER2 protein on the cell surface, while FISH identifies HER2 gene amplification at the DNA level. The objective of this study is to know the prevalence of FISH positive cases in IHC , HER2 equivocal cases of breast cancer. Patients and methods: This descriptive cross sectional study was carried out in Al Hada, Armed Forces Hospital in Taif region for two years. The study includes individuals aged 18 or older classified as HER2-equivocal (IHC 2+) invasive breast cancer per ASCO/CAP guidelines within three months, who provide informed consent for tissue and clinical data use. Exclusions include confirmed HER2-positive or HER2-negative status, insufficient tumor tissue, prior neoadjuvant or HER2-targeted therapy, metastatic disease, severe comorbidities, life expectancy under six months, or inability to consent.. IHC testing was conducted on collected breast tissue with standard protocols. RESULTS: The study analyzed 100 patients aged between 22 and 80 years, with 89% being over the age of 41. The majority of the tumors were identified as ductal carcinoma. Among the patients with HER2-positive equivocal immunostaining, 78% of those results showed no HER2/neu gene amplification on FISH analysis. Conclusion: These findings emphasize the combination of IHC and FISH, to accurately assess HER2 status and guide appropriate treatment decisions